Five Generations in the Workplace: What's a Chairperson to Do? - Robert A Wertkin (Academic Chairpersons Conference Proceedings, 2015)
Having five generations in the academic workplace creates numerous challenges. Understanding generational differences and utilizing effective leadership strategies reduces conflict and enhances the work environment.
Keywords: multiple generations; leadership; conflict resolution; workplace culture; communication